Preservação do patrimônio documental em acervos micrográficos um enfoque no Laboratório de Reprografia da Universidade Federal de Santa Maria - Perlin, Camila Anibale (2013)
This research focuses on the microfilm collection preservation, in the reproduction laboratory of the University of Santa Maria which is part of the documentary heritage of the institution. The intention was to answer the question referring to the appropriate way of keeping safely the microfilm collection of the Laboratory Reproduction, maintaining the preserved information. The exposition to constant climatic changes, characteristic of the region, associated to dirtiness and micro-organisms can cause damage which leads to losing the stored information. The objective general was study the requirements for the correct storing of microforms, aiming the preservation and durability of the micrographic collection of the Federal University of Santa Maria, and ending with the elaboration of Manual with recommendations for the preservation of the micrographic collection. The research was defined as applicable and the approach was qualitative, which included the descriptive analysis of the study of the environment. The first step was the organization of a bibliographic study of the works referring to the subject, along with a study of the history of the Federal University of Santa Maria and all the departments involved with the reproduction laboratory. The research was structured in phases, the first had the objective to investigate the adopted practice in the laboratory referring the keeping and preservation of the cultural heritage, the data resulted into a diagnosis of the Safety Archive of the reproduction laboratory, in which it was possible to identify the preservation needs of the microform cultural heritage. On the second phase of the research, samples of the microfilms and the environment of the Safety Archive were collected. During the research some species of fungi were found in the storage cultural heritage, which is risky for the institution employees and, as well, to the microfilms, in case there are no immediate measures to solve the problem. On the third phase the temperature variation and relative humidity of the Safety Archive were followed. From the obtained date graphics were structured to indicate the different climatic variation in the microfilm storage room, therefore, the use of equipment that guarantees a stable climatic control is necessary, otherwise, the cultural heritage will be vulnerable to fungi proliferation. The research showed that the collection of microforms of the Laboratory Reproduction is contributing some actions to ensure the preservation of information. By studying and knowing the main measures which must be adopted for the preservation it was possible to elaborate the development and the structuration of a Recommendation Manual for the preservation of the micrographic heritage, contributing for the safeguarded of the documental patrimony of the Federal University Of Santa Maria.